Comparison Of Hemorrhagic Stroke Measurement Results In Ct-Scan Modality With Software Volume Evaluation Method And Otsu Thresholding Segmentation Method - Ahmad Ali Bisri; Sidin Haryanto; Dwi Rochmayanti (International Journal Labs, 2024)
Evaluation of CT-scan image results of hemorrhagic strokes was carried out using the volume evaluation software method manually; this method has several weaknesses in that the measurement takes a relatively long time. This researcher applies a digital image processing program with the help of Matlab software by utilizing the segmentation process of the Otsu thresholding method to measure hemorrhagic strokes. To determine differences in the results of hemorrhagic stroke measurements using the software volume evaluation method and the Otsu thresholding method. Quasi-experimental research with a post-test only control group design on CT-scan images. Create an otsu thresholding design using the Matlab R2021a program. Digital images were used as data for 32 CT-Scan images of the head. Processing and analysis of the results in this research used quantitative methods using the Mann-Whitney non-parametric statistical test. Measurement of hemorrhagic stroke using the software volume evaluation method with the Otsu thresholding method shows that there is a difference with a value of 0.04 with a p value < 0.05 and the software volume evaluation method has an average percentage difference of 59% from the Otsu thresholding method. Measurements using volume evaluation software take longer than the automatic Otsu thresholding method, but the results are not better than the volume evaluation software method. The software volume evaluation method is better in measuring hemorrhagic stroke volume compared to the Otsu thresholding method.